Resilience in institutionalized and non-institucionalized children - Gianino Gadea, Lorena (2012)
The present study aimed to establish whether there are differences in resilience, from personal factors, among institutionalized and non-institutionalized children. This is a descriptive and comparative study. The samples were composed of 56 minor children between 8 and 11 years old shelter in Puericultorio Perez Aranibar during 2011 and 56 minor children between 8 and 11 years old who were studying in Peru-Spain School in the district of Villa El Salvador during 2011. The assessment tool used was the Ana Cecilia Salgado Levano Resilience Inventory.The conclusions of this study showed that there are no remarkable differences between the groups of institutionalized and non-institutionalized children in terms of resilience.